Trust, Justice, Ethics Dan Job Performance dalam Perspektif Islam Pada Tenaga Kependidikan Institut Agama Negeri (IAIN) Bengkulu - Khairiah Khairiah (Al-Ulum, 2019)
The article is to depict trust, justice, and ethics to the job performance in Islamic perspective on educational staffs of the State Islamic Institute (Institut Agama Islam Negeri - IAIN) of Bengkulu. This research design using qualitative descriptive method is data collection using a set of instruments; namely interviews, observation and documentation. The results show that trust, justice, ethics in Islamic perspective can improve job performance. It is advisable if one wants to improve the job performance; then, there should be increase the trust, justice, and ethics at the educational staff of the State Islamic Institute Bengkulu.